Impact of COVID-19 infection on the development of type 1 diabetes mellitus in children and adolescents - F. A. Khaydarova; N. U. Alimova; A. V. Alieva; A. S. Sadykova; M. D. Aripova (Сахарный диабет)
Children did not escape the COVID-19 pandemic. Although, in general, the course of viral infection in children is mild, the question of the long-term effects of COVID-19 on a child and adolescent, in particular, on pancreatic beta cells, remains unclear.Аim: Тo study the characteristics of children with diabetes mellitus identified after COVID-19 infection.Materials and methods: This article presents the preliminary results obtained from children and adolescents hospitalized at the RSSPMCE clinic with the newly diagnosed diabetes mellitus after COVID infection, as well as a systematic review of 61 clinical cases (case series study).Results: Of the 120 children hospitalized at the RSSPMCE clinic with newly diagnosed diabetes, 15 were diagnosed with diabetes after COVID-19 infection, all in a state of diabetic ketoacidosis. Only 20% of children knew about the previous COVID-19 infection, the course of the disease was mild, in 80% of children the infection was asymptomatic. At the time of diabetes onset, all children had a high level of HbA1c - above 10%, a low level of vitamin D, high levels of antibodies to SARS-CoV-2 (IgG), and the need for insulin was above the average.Conclusion: The SARS CoV-2 virus could be the direct cause of the development of diabetes mellitus in children, even with the asymptomatic course of the viral infection. However, the question remains about the exact classification of diabetes after COVID-19 in children. It is necessary to inform the population about the first signs and symptoms of diabetes mellitus in order to timely consult a doctor for the diagnosis of diabetes mellitus.